Economic Geography and Spatial Statistics: Theory and Empirics of New Zealand Regions - Suzi Kerr; Jason Timmins (New Zealand Government, The Treasury, 2000)
This paper sets the stage for current Treasury research on New Zealand regional socio-economic issues by: - Outlining a basic theoretical framework; - Introducing a regional database and Geographic Information Systems, a new empirical tool for data analysis; and - Illustrating the potential of this data and tools for analysing policy relevant issues by testing some empirical hypotheses derived from the theoretical framework.
Keywords: 330